Pull-out strength of 0°/30° Kirschner wire syringe external fixators with and without polymer augmentation: A biomechanical study - Atthakomol,P. (Medical Association of Thailand, 2015)
© 2015, Medical Association of Thailand. All rights reserved. Background: Hand external fixators are in use worldwide and insulin syringes can generally be found in an operating room. Objective: To compare the pull-out strength between degrees of Kirschner wire fixation (0° and 30°) and the effect of filling an insulin syringe with polymer. Material and Method: Pull-out strength was compared between a syringe external fixator and a bone or plastic tube model. Fifty-two plastic tube models and 20 dry phalangeal bones were included. The syringe external fixator was attached via two Kirschner wires. Four variations were studied: 0° non-polymer, 0° with polymer augmentation, 30° non-polymer, and 30° with polymer augmentation. The pull-out strength was measured in each group. Results: The strength of polymer augmentation was higher than non-polymer augmentation at 0° (p = 0.0003) and 30° (p = 0.0002). The Kirschner wire at 30° provided more pull-out strength than at 0° (p = 0.0003) using the syringe with no polymer. However, using the syringe with polymer augmentation, there was no significant difference (p = 0.5136). Conclusion: Polymer augmentation significantly increases the pull-out strength at both degrees of fixation. The degree of fixation significantly increases the pull-out strength only in the non-polymer group, where pinning at 30° was superior to 0°.